Value of ultrasound indices for the assessment of rheumatoid arthritis activity and tocilizumab therapy efficiency - Rita Aleksandrovna Osipyants; D E Karateev; E Yu Panasyuk; G V Lukina; E N Aleksandrova; S I Glukhova; A V Volkov; E L Nasonov (Научно-практическая ревматология, 2013)
Objective: to estimate the value of simplified ultrasound (US) indices of synovitis in the most commonly involved joints of the dominant hand, which are studied using the grey scale mode while monitoring the efficiency of tocilizumab (TCZ) therapy in patients with rheumatoid arthritis (RA). Subjects and methods. Forty-six patients with RA confirmed by the 1987 American College of Rheumatology (ACR) criteria who had been ineffectively treated received TCZ infusions for 6 months. The patients were stratified into two groups: 1) 11 patients with early (<2-year) RA (ERA); 2) 35 patients with protracted (>2-year) RA (PRA). Disease activity and therapy efficiency were determined by DAS28-CRP, SDAI, and US study of the dominant hand joints most commonly involved in the pathological process. Results. The evaluation of TCZ therapy from the simplified US indices reflected synovitis regression in the dominant hand joints of patients with ERA. The highly significant correlations between the changes in US parameters and RA activity the indices ^US-wrist/iDAS28-CRP: r = 0.75; p = 0.01; ΔUS-S8/ΔDAS28-CRP and ΔUS-S5/ΔSDAI: r = 0.65; p < 0.05) confirm the validity of the above changes. No reduction in the joint indices was observed in the patients with PRA. Conclusion. The simplified grey-scale US indices of synovitis in the joints of the dominant hand (including one wrist joint) is an accessible noninvasive method for evaluating the efficiency of the therapy performed in patients with ERA.